Königinnen unter missionarischem Erfolgszwang. Salvabitur vir infideli – eine frühmittelalterliche Aktualisierung von 1Kor 7,14a - Felber, Anneliese (Protokolle zur Bibel, 2005)
From the sixth century on a form of salvare (instead of sanctificare) seems to be the preferred text of 1Cor 7:14a, that implies a concrete meaning, i.e. the salvation of the soul. In addition to this the future tense is very appropriate to spur Christian Queens on converting their husbands to Christianity in order to gain the hole people for Catholicism.